2013
DOI: 10.1038/ki.2013.248
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nrf2 in protection against acute kidney injury

Abstract: Multifaceted cell defense pathways perform a critical role in the maintenance of homeostasis at the cellular, tissue, and organism levels. The Keap1-Nrf2 pathway is one of the most important of these cytoprotective pathways, with Nrf2 serving as a master transcriptional regulator of the basal and inducible expression of a multitude of genes encoding detoxification enzymes, antioxidant proteins, xenobiotic transporters, and other stress-response mediators. An increasing body of evidence supports a vital physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(122 citation statements)
references
References 74 publications
3
118
1
Order By: Relevance
“…Multiple studies have documented that induction of Nrf2 is protective for the kidney in CKD, diabetic nephropathy, renal fibrosis, ischemia and other insults. 52 The fact that this was inhibited suggests the acute overload model does not induce stress nor needs the stress response elements increased, thus preventing an over-reaction to this acute protein load. The second upstream regulator inhibited was ANGPT2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have documented that induction of Nrf2 is protective for the kidney in CKD, diabetic nephropathy, renal fibrosis, ischemia and other insults. 52 The fact that this was inhibited suggests the acute overload model does not induce stress nor needs the stress response elements increased, thus preventing an over-reaction to this acute protein load. The second upstream regulator inhibited was ANGPT2.…”
Section: Discussionmentioning
confidence: 99%
“…First, NFE2L2 encodes the protein Nrf2, which is part of the cytoprotective Keap1-Nrf2 pathway. 52 Normally repressed by its association with Keap1-Cul3 complex in the cytoplasm, Nrf2 migrates to the nucleus upon stress induction and binds to specific response elements inducing expression of target genes to detoxify, provide oxidant protection, and other stress response mediators. Multiple studies have documented that induction of Nrf2 is protective for the kidney in CKD, diabetic nephropathy, renal fibrosis, ischemia and other insults.…”
Section: Discussionmentioning
confidence: 99%
“…Even if treatment includes chronic administration of potent Nrf2 inducers, the body does not seem to be impaired. Indeed, many previous studies revealed that pharmacological Nrf2 activation has a protective effect on a variety of stress-mediated diseases, including kidney injury (80,81).…”
Section: Novel Function Of Nrf2mentioning
confidence: 99%
“…[107][108][109][110][111] Although the involved mechanisms are poorly studied, they might involve GSK3-mediated degradation of the transcription factor Nrf2, which upregulates the expression of different antioxidant proteins, like Bcl-2, and recently emerged as an important player in protection against AKI. [112][113][114][115][116] …”
Section: Gsk3 Inhibition Protects Against Oxidative Stress By Regulatmentioning
confidence: 99%